Dynamic alterations in the paternal epigenetic landscape following fertilization - Jenkins, Timothy; Carrell, Douglas T. (Frontiers in Genetics, 2012)
Embryonic development is a complex and dynamic process with frequent changes in gene expression, ultimately leading to cellular differentiation and commitment of various cell lines. These changes are likely preceded by changes to signaling cascades and/or alterations to the epigenetic program in specific cells. The process of epigenetic remodeling begins early in development. In fact, soon after the union of sperm and egg massive epigenetic changes occur across the paternal and maternal epigenetic landscape. The epigenome of these cells includes modifications to the DNA itself, in the form of DNA methylation, as well as nuclear protein content and modification, such as modifications to histones. Sperm chromatin is predominantly packaged by protamines, but following fertilization the sperm pronucleus undergoes remodeling in which maternally derived histones replace protamines, resulting in the relaxation of chromatin and ultimately decondensation of the paternal pronucleus. In addition, active DNA demethylation occurs across the paternal genome prior to the first cell division, effectively erasing many spermatogenesis derived methylation marks. This complex interplay begins the dynamic process by which two haploid cells unite to form a diploid organism. The biology of these events is central to the understanding of sexual reproduction, yet our knowledge regarding the mechanisms involved is extremely limited. This review will explore what is known regarding the post-fertilization epigenetic alterations of the paternal chromatin and the implications suggested by the available literature.